Dinâmica digestiva proteica e resposta de desempenho em jundiá (Rhamdia quelen) - Martinelli, Suziane Ghedini (2013)
The aim of this study was to evaluate the effect of diets with different speeds of protein digestion on performance, composition, metabolic parameters, glucose curve and protein absorption curve of silver catfishes. The effect of adding tannin to experimental diets with rapid digestion protein sources was also evaluated in relation to digestive and metabolic responses. Assays were performed in vitro for selection of protein sources with different digestion rates, which composed the following diets: PS- fishmeal (slow speed digestion) and soybean meal (fast speed digestion), PC: fishmeal and canola meal (average speed of digestion), PCS- fish meal, canola meal and soybean meal, PStan- fish meal and soybean meal (with addition of 1.5% tannin) and PCStan- fishmeal, canola meal and soybean meal (with addition of 1.5% tannin). The biological assay of growth was composed by 375 juvenile catfish (38 ± 3 g initial weight), which were divided into 15 experimental units, composing five treatments with three replications. At the end of 60 days, the animals were weighed and their size measured. Samples of blood, fillet, liver and digestive tract were taken. The proximate analysis of whole fish was also accomplished. Glucose and protein contents were determined in blood samples before feeding and hour after delivery of the experimental diets (2.5% weight), totaling 12 points of analysis. The apparent diet digestibility was determined in the diet and feces with chromium oxide as an indicator. The in vitro digestion analysis show large differences in the digestion of different protein ingredients and diets, as well as animal performance. The PS diet tends to lead to higher performance, higher carcass protein deposition, lower levels of carcass fat and lower protein retention, compared to PC diet. Indexes and hepato-somatic gonad were higher in animals PS diet, compared to PC diet. The PS diet also showed the best results for apparent digestibility, whereas diets with tannin showed the worst protein digestibility. The PCStan diet showed changes in blood parameters, which combined with glucose curve, may show an indication of animal stress. For other analyzes (liver and digestive tract), no differences were observed. Based on these results, we can conclude that: animal performance was not affected by the diets. The animals fed the PS diet had higher protein retention in the carcass. There were changes in blood parameters of animals from treatments with tannin and treatment PS. The addition of tannins in the diets did not improve performance, and its addition worsened the apparent digestibility of the ration.